Circulating Levels of the Short-Chain Fatty Acid Acetate Mediate the Effect of the Gut Microbiome on Visceral Fat - Nogal, Ana; Louca, Panayiotis; Zhang, Xinyuan; Wells, Philippa M.; Steves, Claire J.; Spector, Tim D.; Falchi, Mario; Valdes, Ana M.; Menni, Cristina (Frontiers in Microbiology, 2021)
Background: Acetate is a short-chain fatty acid (SCFA) produced by gut bacteria, which has been implicated in cardio-metabolic health. Here we examine the relationships of circulating acetate levels with gut microbiome composition and diversity and with visceral fat in a large population-based cohort. Results: Microbiome alpha-diversity was positively correlated with circulating acetate levels (Shannon, Beta [95%CI] = 0.12 [0.06, 0.18], P = 0.002) after adjustment for covariates. Six serum acetate-associated bacterial genera were also identified, including positive correlations with Coprococcus, Barnesiella, Ruminococcus and Ruminococcaceae NK4A21 and negative correlations were observed with Lachnoclostridium and Bacteroides. We also identified a correlation between visceral fat and serum acetate levels (Beta [95%CI] = −0.07 [-0.11, -0.04], P = 2.8 x 10-4) and between visceral fat and Lachnoclostridium (Beta [95%CI] = 0.076 [0.042, 0.11], P = 1.44 x 10-5). Formal mediation analysis revealed that acetate mediates ~10% of the total effect of Lachnoclostridium on visceral fat. The taxonomic diversity showed that Lachnoclostridium and Coprococcus comprise at least 18 and 9 species, respectively, including novel bacterial species. By predicting the functional capabilities, we found that Coprococcus spp. present pathways involved in acetate production and metabolism of vitamins B, whereas we identified pathways related to the biosynthesis of trimethylamine (TMA) and CDP-diacylglycerol in Lachnoclostridium spp. Conclusions: Our data indicates that gut microbiota composition and diversity may influence circulating acetate levels and that acetate might exert benefits on certain cardio-metabolic disease risk by decreasing visceral fat. Coprococcus may play an important role in host health by its production of vitamins B and SCFAs, whereas Lachnoclostridium might have an opposing effect by influencing negatively the circulating levels of acetate and being involved in the biosynthesis of detrimental lipid compounds.